EFFECT OF INTELLECTUAL CAPITAL ON PROFITABILITY OF HEALTHCARE FIRMS IN NIGERIA. - Peter Izuchukwu, Ndueche (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study examines the causal effect relationship that exist between intellectual capital and profitability of listed health care firms in NigeriaExchange Group. The study used panel data and adopted ex-post facto research design. Four objectives and hypotheses formulated for the study were tested using data collated from financial report of the health care companies used in the study between 2011 to 2021 fiscal year. The data collated were analysed using regression analysis, however some preliminary analysis such as descriptive statistics, correlation analysis, as well as some diagnostic analysis like Shapiro wilk test normality test were carried out to ascertain the presence of multi-colinearity, and the normality/fitness of the data used. The study finds that intellectual capital components have 53.5% impact on the profitability of health care companies in Nigeria. The finding from the specific objectives indicated that human capital, structural capital and capital employed have positive and significant effect on profitability of health care firms in Nigeria Exchange Group. While relational capital has positive but insignificant effects on profitability of health care firms. Based on the result and findings, the study recommends that management of Health care companies listed on the Nigeria exchange group promotes policies that would attract quality human capital and retaining them as this would enhance the possibility of achieving high profitability.